Tipping a favorable CNS intratumoral immune response using immune stimulation combined with inhibition of tumor-mediated immune suppression. (3rd May 2016) - Kong, Ling-Yuan; Wei, Jun; Fuller, Gregory N.; Schrand, Brett; Gabrusiewicz, Konrad; Zhou, Shouhao; Rao, Ganesh; Calin, George; Gilboa, Eli; Heimberger, Amy B.
ABSTRACT: High-grade gliomas are notoriously heterogeneous regarding antigen expression, effector responses, and immunosuppressive mechanisms. Therefore, combinational immune therapeutic approaches are more likely to impact a greater number of patients and result in longer, durable responses. We have previously demonstrated the monotherapeutic effects of miR-124, which inhibits the signal transducer and activator of transcription 3 (STAT3) immune suppressive pathway, and immune stimulatory 4–1BB aptamers against a variety of malignancies, including genetically engineered immune competent high-grade gliomas. To evaluate potential synergy, we tested an immune stimulatory aptamer together with microRNA-124 (miRNA-124), which blocks tumor-mediated immune suppression, and found survival to be markedly enhanced, including beyond that produced by monotherapy. The synergistic activity appeared to be not only secondary to enhanced CD3 + cell numbers but also to reduced macrophage immune tumor trafficking, indicating that a greater therapeutic benefit can be achieved with approaches that both induce immune activation and inhibit tumor-mediated immune suppression within the central nervous system (CNS) tumors.